Robotic Radiosurgery for Brain Metastases Diagnosed With Either SPACE or MPRAGE Sequence (CYBER-SPACE)—A Single-Center Prospective Randomized Trial. Issue 1 (15th March 2018) - El Shafie, Rami A; Paul, Angela; Bernhardt, Denise; Lang, Kristin; Welzel, Thomas; Sprave, Tanja; Hommertgen, Adriane; Krisam, Johannes; Schmitt, Daniela; Klüter, Sebastian; Schubert, Kai; Klose, Christina; et al.
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) of brain metastases (BM) is recommended in oligometastatic scenarios as a less toxic treatment alternative to whole-brain radiotherapy. Recent findings support SRS for patients with multiple (>3) BM. Furthermore, advances in MR imaging have facilitated the detection of very small BM, as advances in SRS technology have facilitated the highly conformal and simultaneous treatment of multiple target lesions. OBJECTIVE: To compare efficacy and toxicity of repeated frameless robotic SRS of up to 10 simultaneous BM through a single-center prospective randomized trial. METHODS: Two hundred patients will be randomized and receive imaging and treatment based on either the highly sensitive SPACE (sampling perfection with application optimized contrasts using different flip angle evolution) or the MPRAGE (magnetization-prepared rapid gradient-echo) magnetic resonance imaging sequence. If during follow-up new metastases are detected, treatment is repeated. The primary endpoint is reached when a patient develops more than 10 simultaneous new BM and is thus deemed unsuitable for further SRS. Overall survival will be assessed as secondary endpoint. Quality of life and neurocognition will be evaluated every 3 mo using CANTAB tests and EORTC (European Organisation for Research and Treatment of Cancer) questionnaires. EXPECTED OUTCOMES: We expect to show that repeated SRS based on sensitive imaging can delay intracranial dissemination while preserving neurocognitive function and quality of life. DISCUSSION: The present study is the first to prospectively assess the benefit of sensitive imaging and repeated stereotactic irradiation in the treatment of patients with multiple BM. It represents a novel approach, where in a palliative setting advanced technology in treatment and diagnostics is employed to improve tumor control while also reducing toxicity and preserving quality of life.